Vibration Control Devices for Building Structures and Installation Approach: a review - Sarwar, Waseem; Sarwar, Rehan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Retrofit and structural design with vibration control devices have been proven repeatedly to be feasible seismic hazard mitigation approach. To control the structural response; supplemental energy dissipation devices have been most commonly used for energy absorption. The passive control system has been successfully incorporated in mid to high rise buildings as an appropriate energy absorbing system to suppress seismic and wind-induced excitation.
Keywords: building structures; vibrations; control devices; seismic hazard; mechanical behavior; installation approach; design considerations; konstrukcje budowlane; drgania; urządzenia kontrolne; zagrożenie sejsmiczne